Polymer latex for preparing elastomeric films with excellent stress retention and softness
The preparation of polymer latex containing ethylenically unsaturated monomer mixtures by radical emulsion polymerization solves the problem of insufficient stress retention and softness of surgical gloves in the prior art, achieves excellent stress retention and softness, and shows self-healing properties during the heat treatment process.
Patent Information
- Application Number
- CN202080065656.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-20
- Filing Date
- 2020-09-18
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2040-09-18
AI Technical Summary
The prior art is difficult to achieve excellent stress retention and softness in surgical gloves, and conventional XNBR latex exhibits poor adaptability and may lead to cross contamination in surgical gloves.
Polymer latex containing a mixture of ethylenically unsaturated monomers, which contains conjugated dienes, ethylenically unsaturated nitrile compounds, vinyl aromatic monomers, and ethylenically unsaturated acids, are prepared by radical emulsion polymerization.
The elastomer films made from the polymer latex show improved stress retention and softness, are suitable for surgical gloves and other applications, and can exhibit self-healing properties during heat treatment.
Smart Images

Figure BDA0003552794050000211 
Figure BDA0003552794050000271 
Figure BDA0003552794050000282
Abstract
Description
[0001] The present invention relates to a polymer latex for preparing an elastomeric film showing excellent stress retention and softness, to such an elastomeric film and articles containing the elastomeric film, to a latex composition containing the polymer latex, and to a method for manufacturing articles such as dip-molded articles using the film. Background of the Invention
[0003] According to current industry standards, elastomeric films are manufactured from compounds containing carboxylated acrylonitrile butadiene latex (XNBR), particularly in dip molding applications, such as examination gloves. However, such conventional XNBR latexes cannot be used in surgical gloves because gloves manufactured from these conventional latexes have very poor stress retention properties and are very rigid in nature. Poor stress retention results in a poor fit of the glove to the surgeon's forearm, which can lead to cross contamination.
[0004] Therefore, natural latex surgical gloves are often used. However, natural rubber may cause protein allergy problems. Other polymers (such as polyisoprene or polychloroprene) can also be used to make surgical gloves. However, the processing costs for these materials are very high and the production is not environmentally friendly.
[0005] US 6,451,893 relates to a zinc oxide-free elastomer formulation comprising nitrile butadiene latex, 3.0 parts of sulfur per 100 parts of nitrile rubber, and a sulfur vulcanization accelerator. Gloves made from these formulations show improved stress retention properties. In particular, relatively high amounts of sulfur and sulfur vulcanization accelerators may cause allergy problems.
[0006] WO 00 / 21451 discloses carboxylated nitrile rubber gloves with high stress retention, which are made using a pre-vulcanized carboxylated nitrile latex having 2 to 6 wt% methacrylic acid.
[0007] US 2005 / 0154122 describes a two-step polymerization process for making a dip-forming latex resulting in a soft elastomeric film.
[0008] US 2017 / 0099889 relates to gloves showing improved stress retention, made from a formulation containing carboxylated nitrile rubber latex crosslinked by aluminum ions. Aluminum ions are considered a potential health hazard.
[0009] According to US 7,730,554 gloves showing improved stress retention can be manufactured by a double dipping process, using different XNBR latexes in two dipping steps. This method is complex and leads to increased production costs.
[0010] It is therefore an object of the present invention to provide a polymer latex which yields an elastomeric film having excellent stress retention properties and superior softness and which can be used in a range of articles, but in particular they are suitable for use in surgical gloves and condom applications. SUMMARY OF THE INVENTION
[0012] The present inventors have surprisingly found that elastomeric films made from polymer latex obtainable by free radical emulsion polymerization of a mixture of ethylenically unsaturated monomers, comprising:
[0013] a) 15 to 99 wt% of a conjugated diene;
[0014] b) 0 to 80 wt % of an ethylenically unsaturated nitrile compound;
[0015] c) 0 to 70 wt% of a vinyl aromatic monomer;
[0016] The sum of the ethylenically unsaturated nitrile compound b) and the vinyl aromatic monomer c) is 0.95 to 84.95 wt %,
[0017] d) 0.05 to 10 wt% of an ethylenically unsaturated acid, wherein the ethylenically unsaturated acid comprises
[0018] d1) contains the following ethylenically unsaturated acids:
[0019] - an acid functional group; and
[0020] - a spacer group separating the ethylenically unsaturated group from the acid functional group by at least 4 atoms; and
[0021] e) 0 to 65 wt % of a copolymerizable ethylenically unsaturated compound,
[0022] Therein the monomers a) to e) are different from one another and the percentages by weight are based on the total monomers in the mixture.
[0023] According to one aspect, the present invention relates to a polymer latex obtainable by free radical emulsion polymerization of an ethylenically unsaturated monomer mixture comprising:
[0024] a) 15 to 99 wt% of a conjugated diene;
[0025] b) 0 to 80 wt % of an ethylenically unsaturated nitrile compound;
[0026] c) 0 to 70 wt% of a vinyl aromatic monomer;
[0027] The sum of the ethylenically unsaturated nitrile compound b) and the vinyl aromatic monomer c) is 0.95 to 84.95 wt %,
[0028] d) 0.05 to 10 wt% of an ethylenically unsaturated acid, wherein the ethylenically unsaturated acid comprises
[0029] d1) Containing the following ethylenically unsaturated acids
[0030] - an acid functional group; and
[0031] - a spacer group separating the ethylenically unsaturated group from the acid functional group by at least 4 atoms; and
[0032] e) 0 to 65 wt % of a copolymerizable ethylenically unsaturated compound,
[0033] The monomers a) to e) are different from one another and the percentages by weight are based on the total monomers.
[0034] According to a further aspect, the invention relates to the use of the polymer latex for producing dip-molded articles or for coating or impregnating substrates, preferably textile or ceramic substrates.
[0035] According to a further aspect, the present invention relates to a polymer latex composition comprising the polymer latex of the present invention, wherein monomer d) comprises an ethylenically unsaturated carboxylic acid and the composition further comprises an oxirane functional compound.
[0036] According to a further aspect, the present invention relates to a compounded latex composition suitable for producing dip molded articles, which contains the polymer latex or polymer latex composition as defined above and optionally an auxiliary agent selected from sulfur vulcanizing agents, accelerators for sulfur vulcanization, crosslinking agents, multivalent cations and combinations thereof.
[0037] According to a further aspect, the present invention relates to a method for producing a dip-molded article by the following steps:
[0038] a) providing a compounded latex composition as defined above;
[0039] b) immersing a mold having the desired shape of the final article in a coagulant bath containing a metal salt solution;
[0040] c) removing the mold from the coagulant bath and optionally drying the mold;
[0041] d) dipping the mold treated in steps b) and c) into the compounded latex composition of step a);
[0042] e) causing the latex film to coagulate on the surface of the mold;
[0043] f) removing the latex-coated mold from the compounded latex composition and optionally immersing the latex-coated mold in a water bath;
[0044] g) optionally drying the latex-coated mold;
[0045] h) heat treating the latex-coated mold obtained from step e) or f) at a temperature of 40°C to 180°C, preferably 60°C to 100°C; and
[0046] i) Removing the latex article from the mould.
[0047] Yet a further aspect of the present invention relates to an elastomeric film made from the polymer latex, polymer latex composition or compounded latex composition of the present invention, and to an article comprising the elastomeric film, which is preferably selected from surgical gloves, examination gloves, condoms, catheters, industrial gloves, textile-supported gloves and household gloves. DETAILED DESCRIPTION OF THE INVENTION
[0049] The polymer latex according to one aspect of the present invention may be obtained by free radical emulsion polymerization of an ethylenically unsaturated monomer mixture comprising:
[0050] a) 15 to 99 wt% of a conjugated diene;
[0051] b) 0 to 80 wt % of an ethylenically unsaturated nitrile compound;
[0052] c) 0 to 70 wt% of a vinyl aromatic monomer;
[0053] The sum of the ethylenically unsaturated nitrile compound b) and the vinyl aromatic monomer c) is 0.95 to 84.95 wt %,
[0054] d) 0.05 to 10 wt% of an ethylenically unsaturated acid, wherein the ethylenically unsaturated acid comprises
[0055] d1) contains the following ethylenically unsaturated acids:
[0056] -Acid functional group
[0057] - a spacer group separating the ethylenically unsaturated group and the acid functional group by at least 4 atoms; and
[0058] e) 0 to 65 wt % of a copolymerizable ethylenically unsaturated compound,
[0059] The monomers a) to e) are different from one another and the weight percentages are based on the total monomers.
[0060] The conjugated diene monomers a) suitable for preparing the polymer latex of the present invention include conjugated diene monomers selected from the group consisting of 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, 2,4-hexadiene, 1,3-octadiene, 2-methyl-1,3-pentadiene, 2,3-dimethyl-1,3-pentadiene, 3,4-dimethyl-1,3-hexadiene, 2,3-diethyl-1,3-butadiene, 4,5-diethyl-1,3-octadiene, 3-butyl-1,3-octadiene, 3,7-dimethyl-1,3,6-octatriene, 2,4-hexadiene, 1,3-octadiene, 2,3-di ... 1,3-Butadiene, isoprene and combinations thereof are preferred conjugated dienes. 1,3-Butadiene is the most preferred diene. Typically, the conjugated diene monomer is used in an amount ranging from 15 to 99 wt%, preferably 20 to 99 wt%, more preferably 30 to 75 wt%, and most preferably 40 to 70 wt%, based on the total weight of the monomers. Thus, the conjugated diene may be present in an amount of at least 15 wt%, at least 20 wt%, at least 22 wt%, at least 24 wt%, at least 26 wt%, at least 28 wt%, at least 30 wt%, at least 32 wt%, at least 34 wt%, at least 36 wt%, at least 38 wt%, or at least 40 wt%, based on the total weight of the ethylenically unsaturated monomers used in the polymer latex.
[0061] Therefore, the consumption of this conjugated diene monomer can be no more than 95wt%, no more than 90wt%, no more than 85wt%, no more than 80wt%, no more than 78wt%, no more than 76wt%, no more than 74wt%, no more than 72wt%, no more than 70wt%, no more than 68wt%, no more than 66wt%, no more than 64wt%, no more than 62wt%, no more than 60wt%, no more than 58wt%, or no more than 56wt%.It will be appreciated by those skilled in the art that the present invention discloses any scope between any clearly disclosed lower limit and the upper limit.
[0062] Unsaturated nitrile monomers that can be used to make particles of latex polymer (a) include polymerizable unsaturated aliphatic nitrile monomers containing 2 to 4 carbon atoms in a linear or branched arrangement, which may be substituted with acetyl or additional nitrile groups. Such nitrile monomers include acrylonitrile, methacrylonitrile, α-cyanoethylacrylonitrile, fumaronitrile, and combinations thereof, with acrylonitrile being most preferred. These nitrile monomers may be included in an amount of 0 to 80 wt%, preferably 1 to 80 wt%, more preferably 10 to 70 wt%, or 10 to 60 wt%, and more preferably 15 to 50 wt%, even more preferably 20 to 50 wt%, and most preferably 23 to 43 wt%, based on the total weight of the ethylenically unsaturated monomers used in the polymer latex.
[0063] Thus, the unsaturated nitrile can be present in an amount of at least 1 wt%, 5 wt%, at least 10 wt%, at least 12 wt%, at least 14 wt%, at least 16 wt%, at least 18 wt%, at least 20 wt%, at least 22 wt%, at least 24 wt%, at least 26 wt%, at least 28 wt%, at least 30 wt%, at least 32 wt%, at least 34 wt%, at least 36 wt%, at least 38 wt%, or at least 40 wt%, based on the total weight of the ethylenically unsaturated monomers used in the polymer latex.
[0064] Therefore, the amount of this unsaturated nitrile monomer can be no more than 80wt%, no more than 75wt%, no more than 73wt%, no more than 70wt%, no more than 68wt%, no more than 66wt%, no more than 64wt%, no more than 62wt%, no more than 60wt%, no more than 58wt%, no more than 56wt%, no more than 54wt%, no more than 52wt%, no more than 50wt%, no more than 48wt%, no more than 46wt%, or no more than 44wt%.Those skilled in the art will appreciate that the present invention discloses any scope between the lower limit and the upper limit clearly disclosed.
[0065] Representative vinyl-aromatic monomers (c) include, for example, styrene, α-methylstyrene, vinyltoluene, o-methylstyrene, p-methylstyrene, p-tert-butylstyrene, 2,4-dimethylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, 2,4-diisopropylstyrene, 2,4-dimethylstyrene, 4-tert-butylstyrene, 5-tert-butyl-2-methylstyrene, 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, 4-bromostyrene, 2-methyl-4,6-dichlorostyrene, 2,4-dibromostyrene, vinyl phthalate, vinyltoluene and vinylxylene, 2-vinylpyridine, 4-vinylpyridine and 1,1-diphenylethylene and substituted 1,1-diphenylethylene, 1,2-diphenylethylene and substituted 1,2-diphenylethylene. Mixtures of one or more vinyl-aromatic compounds may also be used. Preferred monomers are styrene and α-methylstyrene. The amount of the vinyl-aromatic compound can range from 0 to 70 wt%, preferably 1 to 70 wt%, more preferably 10 to 70 wt%, even more preferably 15 to 60 wt%, even more preferably 15 to 50 wt%, or 0 to 25 wt%, more preferably 0 to 15 wt%, and even more preferably 0 to 10 wt%, based on the total weight of the ethylenically unsaturated monomers used in the polymer latex. Thus, the vinyl-aromatic compound can be present in an amount of no more than 60 wt%, no more than 50 wt%, no more than 40 wt%, 35 wt%, no more than 30 wt%, no more than 25 wt%, no more than 20 wt%, no more than 18 wt%, no more than 16 wt%, no more than 14 wt%, no more than 12 wt%, no more than 10 wt%, no more than 8 wt%, no more than 6 wt%, no more than 4 wt%, no more than 2 wt%, or no more than 1 wt%, based on the total weight of the ethylenically unsaturated monomers used in the polymer latex. If present, the vinyl aromatic compound can be present in an amount of 1 wt%, at least 2 wt%, at least 5 wt%, at least 10 wt%, at least 15 wt%, at least 20 wt%, at least 25 wt%, at least 30 wt%, or at least 35 wt%, based on the total weight of ethylenically unsaturated monomers used in the polymer latex.
[0066] In the monomer mixture for preparing the polymer latex of the present invention, the sum of ethylenically unsaturated nitrile compound b) and vinyl aromatic monomer c) is 0.95 to 84.95wt% based on the total monomers in the mixture. Therefore, vinyl-aromatic compound can also be completely absent. In this case, ethylenically unsaturated nitrile compound is forced to exist and the latex can be regarded as XNBR latex. Alternatively, ethylenically unsaturated nitrile compound can be completely absent. In this case, vinyl aromatic monomer is forced to exist and the latex (especially if butadiene is selected as the preferred conjugated diene and styrene is selected as the preferred vinyl aromatic monomer) can be regarded as XSBR latex.
[0067] The monomer mixture used to prepare the polymer latex of the present invention contains 0.05 to 10 wt% of an ethylenically unsaturated acid (d), wherein the ethylenically unsaturated acid includes an ethylenically unsaturated acid (d1) containing the following:
[0068] - an acid functional group; and
[0069] - a spacer group which separates the ethylenically unsaturated group and the acid functional group by at least 4 atoms.
[0070] The acid functional group may be selected from carboxylic acid groups and phosphorus-containing acid groups. Suitable phosphorus-containing acid groups may be selected from phosphoric acid groups and phosphonic acid groups. Preferably, the acid functional group is selected from carboxylic acid groups.
[0071] The monomer d1) can be selected from compounds having the following structures:
[0072] CHR 2 =CR 1 -AX,
[0073] in
[0074] R 1 is selected from H and C1-C4 alkyl,
[0075] R 2 Selected from H or -AX;
[0076] A is a divalent spacer group which, when present, independently separates the ethylenically unsaturated group and the functional group X by at least 4 atoms, selected from:
[0077] -(C(O)-W) n -Y-(O) m -;-(C(O)-W) n -YOC(O)-Y- and -(CH2) k -O-(C(O)) p -Y-(O) m -
[0078] n, m, k and p are integers independently selected from 0 or 1 at each occurrence;
[0079] W is -O- or -NR 3 -;
[0080] R 3 Selected from H and C1-C4 alkyl;
[0081] Y, when present, is independently selected from an optionally substituted linear, branched, cyclic or aromatic C2-C 3O divalent hydrocarbon or heterohydrocarbon group;
[0082] X is selected from -C(O)OH and -P(O)(OH)2;
[0083] Provided that: if X is -C(O)OH then m is 0; or
[0084] -AX is selected from -C(O)-O-(YC(O)-O) l -H, wherein l is an integer from 2 to 10, preferably from 2 to 7; and
[0085] A mixture of them.
[0086] Preferably, d1) is selected from (meth)acrylic acid carboxyl (C2-C 30 ) alkyl esters, C7-C 15 Mono(meth)acryloyloxyalkyl esters of fatty acids and dicarboxylates, and more preferably selected from (meth)acrylic acid carboxyl (C2-C 12 ) alkyl ester and succinic acid ω-(meth)acryloyloxy (C2-C 12 ) alkyl esters, and most preferably selected from 2-(meth)acryloyloxyethyl succinate, 2-carboxyethyl acrylate and 2-(meth)acryloyloxyethyl succinate and 2-(meth)acryloyloxy ... l -H (l is an integer from 2 to 7) and mixtures thereof.
[0087] Suitable monomers d1) are commercially available from Solvay (Belgium), for example β-CEA, PAM 100, PAM 200, PAM 300, PAM 4000, PAM 5000.
[0088] Typically, the amount of ethylenically unsaturated acid (d) is 0.05 to 10 wt%, particularly 0.1 to 10 wt%, or 0.05 to 7 wt%, preferably 0.1 to 9 wt%, more preferably 0.1 to 8 wt%, even more preferably 1 to 7 wt%, most preferably 2 to 7 wt%, based on the total weight of the ethylenically unsaturated monomers used in the polymer. Thus, the ethylenically unsaturated acid may be present in an amount of at least 0.01 wt%, at least 0.05 wt%, at least 0.1 wt%, at least 0.3 wt%, at least 0.5 wt%, at least 0.7 wt%, at least 0.9 wt%, at least 1 wt%, at least 1.2 wt%, at least 1.4 wt%, at least 1.6 wt%, at least 1.8 wt%, at least 2 wt%, at least 2.5 wt%, or at least 3 wt%. Likewise, the ethylenically unsaturated acid may be present in an amount no greater than 10 wt%, no greater than 9.5 wt%, no greater than 9 wt%, no greater than 8.5 wt%, no greater than 8 wt%, no greater than 7.5 wt%, no greater than 7 wt%, no greater than 6.5 wt%, no greater than 6 wt%, no greater than 5.5 wt%, or no greater than 5 wt%, based on the total weight of the ethylenically unsaturated monomers used in the polymer latex. Those skilled in the art will appreciate that the present invention discloses any range between any explicitly disclosed lower and upper limits.
[0089] The ethylenically unsaturated acid of d1) may be present in the ethylenically unsaturated monomer mixture in an amount of 0.05 to 10 wt %, preferably 0.1 to 9 wt %, more preferably 1 to 8 wt %, more preferably 1 to 6 wt %, even more preferably 2 to 5 wt %, most preferably 2 to 4 wt %, based on the total monomers of the mixture. According to the present invention, the ethylenically unsaturated acid of d1) may be the only ethylenically unsaturated acid.
[0090] Thus, the ethylenically unsaturated acid (d1) may be present in an amount of at least 0.01 wt%, at least 0.05 wt%, at least 0.1 wt%, at least 0.3 wt%, at least 0.5 wt%, at least 0.7 wt%, at least 0.9 wt%, at least 1 wt%, at least 1.2 wt%, at least 1.4 wt%, at least 1.6 wt%, at least 1.8 wt%, at least 2 wt%, at least 2.5 wt%, or at least 3 wt%. Similarly, the ethylenically unsaturated acid (d1) may be present in an amount of no more than 10 wt%, no more than 9.5 wt%, no more than 9 wt%, no more than 8.5 wt%, no more than 8 wt%, no more than 7.5 wt%, no more than 7 wt%, no more than 6.5 wt%, no more than 6 wt%, no more than 5.5 wt%, or no more than 5 wt%, based on the total weight of the ethylenically unsaturated monomers used in the polymer latex. Those skilled in the art will appreciate that the present invention discloses any range between any explicitly disclosed lower and upper limits.
[0091] The monomer mixture for preparing the polymer latex of the present invention may additionally contain an ethylenically unsaturated acid (d2) different from the ethylenically unsaturated acid (d1). Suitable ethylenically unsaturated carboxylic acids (d2) or salts thereof may be selected from monocarboxylic acid and dicarboxylic acid monomers and their anhydrides and partial esters of polycarboxylic acids. It is preferred to use ethylenically unsaturated aliphatic mono- or dicarboxylic acids or anhydrides containing 3 to 5 carbon atoms. Examples of monocarboxylic acid monomers include acrylic acid, methacrylic acid, crotonic acid, and examples of dicarboxylic acid monomers include fumaric acid, itaconic acid, maleic acid, cis-cyclohexene-1,2-dicarboxylic acid, dimethylmaleic acid, bromomaleic acid, 2,3-dichloromaleic acid and (2-dodecene-1-yl) succinic acid. The example of polycarboxylic acid partial ester comprises monomethyl maleate, monomethyl fumarate, monoethyl maleate, monoethyl fumarate, monopropyl maleate, monopropyl fumarate, monobutyl maleate, monobutyl fumarate, maleic acid list (2-ethylhexyl) ester, fumaric acid list (2-ethylhexyl) ester.The example of other suitable ethylenically unsaturated acids (d2) comprises vinylacetic acid, vinyl lactic acid, vinyl sulfonic acid, 2-methyl-2-propylene-1-sulfonic acid, styrene sulfonic acid, acrylamidomethylpropanesulfonic acid and its salt.Particularly preferred (methyl) acrylic acid, crotonic acid, itaconic acid, maleic acid, fumaric acid and their combination.
[0092] The ethylenically unsaturated acid (d2) may be present in the monomer mixture for preparing the polymer latex of the present invention in an amount which together with the amount of the ethylenically unsaturated acid (d1) will provide the total amount of ethylenically unsaturated monomers as disclosed above.
[0093] According to the present invention, it is particularly preferred that the latex particles exhibit a concentration gradient of functional groups (a) with a higher concentration of functional groups (a) at the surface of the particle and a lower concentration in the bulk of the particle.
[0094] Furthermore, the ethylenically unsaturated monomer mixture for the polymer latex according to the present invention may include additional ethylenically unsaturated monomers different from the monomers defined above. These monomers may be selected from:
[0095] e1) alkyl esters of ethylenically unsaturated acids;
[0096] e2) hydroxyalkyl esters of ethylenically unsaturated acids;
[0097] e3) amides of ethylenically unsaturated acids;
[0098] e4) vinyl carboxylates;
[0099] e5) alkoxyalkyl esters of ethylenically unsaturated acids;
[0100] e6) monomers having at least two ethylenically unsaturated groups;
[0101] e7) ethylenically unsaturated silanes; and combinations thereof.
[0102] Carboxylic acid vinyl ester monomers that can be used according to the present invention include vinyl acetate, vinyl propionate, vinyl butyrate, vinyl benzoate, vinyl 2-ethylhexanoate, vinyl stearate, and vinyl esters of versatic acid. The most preferred vinyl ester monomer used in the present invention is vinyl acetate. Typically, the vinyl ester monomer is present in an amount of no more than 18 wt%, no more than 16 wt%, no more than 14 wt%, no more than 12 wt%, no more than 10 wt%, no more than 8 wt%, no more than 6 wt%, no more than 4 wt%, no more than 2 wt%, or no more than 1 wt%, based on the total weight of the ethylenically unsaturated monomers used in the polymer latex.
[0103] Ethylenically unsaturated acid alkyl esters that can be used according to the invention include n-alkyl, isoalkyl or tertiary alkyl esters of acrylic acid or (meth)acrylic acid, wherein the alkyl group has 1 to 20 carbon atoms, reaction products of methacrylic acid with glycidyl esters of neoacids such as versatic acid, neodecanoic acid or pivalic acid, and hydroxyalkyl (meth)acrylate and alkoxyalkyl (meth)acrylate monomers.
[0104] Generally speaking, the preferred alkyl (meth)acrylates can be selected from C1-C 10 Alkyl esters, preferably C1-C8 alkyl (meth)acrylates. Examples of such acrylate monomers include n-butyl acrylate, sec-butyl acrylate, ethyl acrylate, hexyl acrylate, tert-butyl acrylate, 2-ethylhexyl acrylate, isooctyl acrylate, 4-methyl-2-pentyl acrylate, 2-methylbutyl acrylate, methyl methacrylate, butyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, ethyl methacrylate, isopropyl methacrylate, hexyl methacrylate, cyclohexyl methacrylate, and hexadecyl methacrylate. Methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and combinations thereof are preferred.
[0105] Typically, the amount of alkyl (meth)acrylate monomer present, based on the total weight of ethylenically unsaturated monomers used in the polymer latex, can be no more than 18 wt%, no more than 16 wt%, no more than 14 wt%, no more than 12 wt%, no more than 10 wt%, no more than 8 wt%, no more than 6 wt%, no more than 4 wt%, no more than 2 wt%, or no more than 1 wt%.
[0106] The hydroxyalkyl esters of ethylenically unsaturated acids that can be used to prepare the polymer latex of the present invention include hydroxyalkyl acrylates and hydroxyalkyl methacrylate monomers based on ethylene oxide, propylene oxide and higher alkylene oxides or mixtures thereof. Examples are hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate and hydroxybutyl acrylate. Preferably, the hydroxyalkyl (meth)acrylate monomer is 2-hydroxyethyl (meth)acrylate. Typically, the amount of the hydroxyalkyl (meth)acrylate monomer present, based on the total weight of the ethylenically unsaturated monomers used in the polymer latex, can be no more than 18 wt%, no more than 16 wt%, no more than 14 wt%, no more than 12 wt%, no more than 10 wt%, no more than 8 wt%, no more than 6 wt%, no more than 4 wt%, no more than 2 wt%, or no more than 1 wt%.
[0107] The (meth) alkoxyalkyl ester monomers that can be used in the present invention include methoxyethyl methacrylate, ethoxyethyl methacrylate, methoxyethyl methacrylate, ethoxyethyl acrylate, butoxyethyl methacrylate, methoxybutyl acrylate, and methoxyethoxyethyl acrylate. Preferred (meth) alkoxyalkyl ester monomers are ethoxyethyl acrylate and methoxyethyl acrylate. Typically, the amount of the (meth) alkoxyethyl alkyl ester monomer used, based on the total weight of the ethylenically unsaturated monomers used in the polymer latex, can be no more than 18 wt%, no more than 16 wt%, no more than 14 wt%, no more than 12 wt%, no more than 10 wt%, no more than 8 wt%, no more than 6 wt%, no more than 4 wt%, no more than 2 wt%, or no more than 1 wt%.
[0108] The ethylenically unsaturated acid amides that can be used to prepare the polymer latex of the present invention include acrylamide, methacrylamide and diacetone acrylamide. The preferred amide monomer is (meth) acrylamide. In order to introduce functional groups that can self-crosslink into the polymer particles of the present invention during heat treatment, monomers containing N-hydroxymethylamide groups can be used. Suitable monomers are N-hydroxymethyl (meth) acrylamide, N-methoxymethyl-(meth) acrylamide, N-n-butoxy-methyl-(meth) acrylamide, N-isobutoxy-methyl-(meth) acrylamide, N-acetoxymethyl-(meth) acrylamide, N (-2,2-dimethoxy-1-hydroxyethyl) acrylamide. Typically, the amount of ethylenically unsaturated acid amide present, based on the total weight of the ethylenically unsaturated monomers of the polymer latex, can be no more than 18wt%, no more than 16wt%, no more than 14wt%, no more than 12wt%, no more than 10wt%, no more than 8wt%, no more than 6wt%, no more than 4wt%, no more than 2wt%, or no more than 1wt%.
[0109] Suitable monomers (e6) with at least two ethylenically unsaturated groups can be selected from divinylbenzene and diacrylates and di(meth)acrylates. Examples are ethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, tripropylene glycol di(meth)acrylate, butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, and dipropylene glycol di(meth)acrylate. Monomers with at least two ethylenically unsaturated groups are preferably selected from divinylbenzene, 1,2-ethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, and 1,6-hexanediol di(meth)acrylate. Preferred monomers with at least two ethylenically unsaturated groups are preferably selected from divinylbenzene, ethylene glycol dimethacrylate, and 1,4-butanediol di(meth)acrylate. The amount of monomers having at least two ethylenically unsaturated groups may be less than 5 wt%, preferably less than 4 wt%, more preferably less than 3 wt%, even more preferably less than 2.5 wt%, even more preferably less than 2 wt%, even more preferably less than 1.5 wt%, based on the total weight of the monomers. The monomer mixture may be free of monomer e6).
[0110] Suitable silane monomers e7) can be selected from vinyltrialkoxysilane, allyltrialkoxysilane and 3-(meth)acryloxypropyltrialkoxysilane. The amount of silane monomer e7) can be less than 5wt%, preferably less than 4wt%, more preferably less than 3wt%, even more preferably less than 2.5wt%, even more preferably less than 2wt%, even more preferably less than 1.5wt%, based on the total weight of the monomers. The monomer mixture can be free of monomer e7).
[0111] Method for preparing the polymer latex of the present invention:
[0112] The polymer latex of the invention can be prepared by any emulsion polymerization process known to the person skilled in the art, provided that the monomer mixture defined herein is employed. Particularly suitable is the process as described in EP-A 792 891.
[0113] In the emulsion polymerization for preparing the polymer latex of the present invention, a seed latex can be used. Preferably, the seed latex is prepared independently, and the emulsion polymerization is carried out in the presence of the independently prepared seed latex. The seed latex particles are preferably present in an amount of 0.01 to 10, preferably 1 to 5 parts by weight based on 100 parts by weight of the total ethylenically unsaturated monomers used in the polymer latex (including those used to make the seed particles (such as ethylene oxide functionalized latex particles (b))). The lower limit of the amount of the seed latex particles can therefore be 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, or 2.5 parts by weight. The upper limit of the amount can be 10, 9, 8, 7, 6, 5.5, 5, 4.5, 4, 3.8, 3.6, 3.4, 3.3, 3.2, 3.1 or 3 parts by weight. Those skilled in the art will understand that any range formed by any explicitly disclosed lower and upper limits is explicitly included in this specification.
[0114] The process for preparing the polymer latex described above can be carried out at a temperature of 0 to 130° C., preferably 0 to 100° C., particularly preferably 5 to 70° C., very particularly preferably 5 to 60° C., in the absence of one or more emulsifiers, in the absence of one or more colloids and one or more initiators. This temperature includes all values and subvalues therebetween, in particular including 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120 and 125° C.
[0115] Initiators that can be used when carrying out the present invention include water-soluble and / or oil-soluble initiators that are effective for polymerization purposes. Representative initiators are well known in the art and include, for example: azo compounds (such as, for example, AIBN, AMBN and cyanovaleric acid) and inorganic peroxy compounds (such as hydrogen peroxide, sodium, potassium and ammonium peroxydisulfates, peroxycarbonates and peroxyborates), and organic peroxy compounds (such as alkyl hydroperoxides, dialkyl peroxides, acyl hydroperoxides, and diacyl peroxides), and esters (such as tert-butyl perbenzoate) and combinations of inorganic and organic initiators.
[0116] The amount of initiator is sufficient to initiate polymerization at the desired rate. Generally, 0.01 to 5, preferably 0.1 to 4 wt % of initiator is sufficient based on the weight of the total polymer. The amount of initiator is most preferably 0.01 to 2 wt % based on the total weight of the polymer. The amount of initiator includes all values and subvalues therebetween, particularly including 0.01, 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 4 and 4.5 wt % based on the total weight of the polymer.
[0117] The inorganic and organic peroxy compounds mentioned above can also be used alone or in combination with one or more suitable reducing agents, as is well known in the art. Examples of such reducing agents which may be mentioned are sulfur dioxide, alkali metal disulfites, alkali metal bisulfites and ammonium bisulfites, thiosulfates, dithionites and formaldehyde bisulfites, as well as hydroxylamine hydrochloride, hydrazine sulfate, iron (II) sulfate, cuprous naphthenate, glucose, sulfonic acid compounds (such as sodium methanesulfonate), amine compounds (such as dimethylaniline) and ascorbic acid. More preferably, the exclusive sodium salts of organic sulfinic acid derivatives (such as FF6 or FF6M). The reducing agent is preferably used in an amount of 0.03 to 10 parts by weight per part by weight of the polymerization initiator.
[0118] The surfactant or emulsifying agent that is suitable for stabilizing this latex particle comprises those conventional surfactants that are used for polymerization process.One or more surfactants can be added in water and / or monomer phase.In seed method, the effective amount of surfactant is to be selected to support and stabilize this particle as colloid, minimize the contact between this particle and prevent the consumption of coagulation.In non-seed method, the effective amount of surfactant is the consumption selected in order to influence particle size.
[0119] Representative surfactants include saturated and ethylenically unsaturated sulfonic acids or their salts, including, for example, unsaturated hydrocarbon sulfonic acids (such as vinyl sulfonic acid, allyl sulfonic acid and methallyl sulfonic acid and their salts); aromatic hydrocarbon acids (such as, for example, p-styrene sulfonic acid, isopropenylbenzenesulfonic acid and vinyloxybenzenesulfonic acid and their salts); sulfoalkyl esters of acrylic acid and methacrylic acid (such as, for example, sulfoethyl methacrylate and sulfopropyl methacrylate and their salts, and 2-acrylamido-2-methylpropanesulfonic acid and its salts); alkylated diphenyl oxide disulfonates, sodium dodecylbenzenesulfonate and dihexyl ester of sodium sulfosuccinate, sodium alkyl esters of sulfonic acids, ethoxylated alkylphenols and ethoxylated alcohols; fatty alcohol (poly) ether sulfates.
[0120] The type and amount of the surfactant are typically determined by the number of particles, their size and their composition. Typically, the amount of the surfactant is 0 to 20, preferably 0 to 10, more preferably 0 to 5 (wt%) based on the total weight of the monomer. The amount of surfactant includes all values and subvalues therebetween, particularly including 0, 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 and 19 wt% based on the total weight of the monomer. According to one embodiment of the present invention, polymerization is carried out without the use of a surfactant.
[0121] Instead of or in addition to the surfactants described above, various protective colloids may be used. Suitable colloids include polyhydroxy compounds such as partially acetylated polyvinyl alcohol, casein, hydroxyethyl starch, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, polysaccharides and degraded polysaccharides, polyethylene glycol and gum arabic. Preferred protective colloids are carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose. Generally speaking, these protective colloids are used in an amount of 0 to 10, preferably 0 to 5, more preferably 0 to 2 parts by weight based on the total weight of the monomer. The amount of protective colloid includes all values and subvalues therebetween, particularly including 1, 2, 3, 4, 5, 6, 7, 8 and 9 wt % based on the total weight of the monomer.
[0122] Those skilled in the art will appreciate the types and amounts of monomers with polar functional groups, surfactants and protective colloids that are selected to make polymer latexes of the present invention suitable for dip molding applications. Thus, it is preferred that the polymer latex compositions of the present invention have a specific maximum electrolyte stability, which is determined as a critical coagulation concentration (measured at pH 10 and 23° C. for 0.1% total solids content of the composition) of less than 30 mmol / l CaCl2, preferably less than 25 mmol / l, more preferably less than 20 mmol / l, and most preferably less than 10 mmol / l.
[0123] If the electrolyte stability is too high, it will be difficult to coagulate the polymer latex in the dip molding process, resulting in either failure to form a continuous film of the polymer latex on the dipped mold or an uneven thickness of the resulting product.
[0124] It is within the routine skill of those skilled in the art to appropriately adjust the electrolyte stability of the polymer latex. The stability of the electrolyte will depend on certain different factors, such as the amount and selection of monomers (especially monomers containing polar functional groups) to be used to make the polymer latex, and the selection and amount of the stabilizing system (e.g., the emulsion polymerization process used to make the polymer latex). The stabilizing system may contain surfactants and / or protective colloids.
[0125] To achieve the electrolyte stability of the present invention, one skilled in the art can adjust the stabilizing system depending on the monomers selected and their relative amounts used to make the polymer latex of the present invention.
[0126] Since there are so many different influences on the electrolyte stability, adjustments are best made by trial and error. However, as described above, this can be easily done without any undue effort using the electrolyte stability test method.
[0127] It is often recommended to additionally carry out the emulsion polymerization in the presence of buffer substances and chelating agents. Suitable substances are, for example, alkali metal carbonates and bicarbonates, alkali metal phosphates and pyrophosphates (buffer substances) and alkali metal salts of ethylenediaminetetraacetic acid (EDTA) or hydroxy-2-ethylenediaminetriacetic acid (HEEDTA) as chelating agents. The amount of buffer substances and chelating agents is usually 0.001 to 1.0% by weight, based on the total amount of monomers.
[0128] Furthermore, it may be advantageous to use chain transfer agents (regulators) in the emulsion polymerization. Typical agents are, for example, organic sulfur compounds (such as thioesters, 2-mercaptoethanol, 3-mercaptopropionic acid and C1-C 12 If present, the chain transfer agent is generally used in an amount of 0.05-3.0 wt%, preferably 0.2-2.0 wt%, based on the total weight of the monomers used.
[0129] Furthermore, partial neutralization may be beneficially introduced into the polymerization process. Those skilled in the art will appreciate that by appropriate selection of this parameter, the necessary control may be achieved.
[0130] Polymer latex composition
[0131] The polymer latex composition of the present invention can be prepared by first making a polymer latex as described above (wherein monomer d) comprises an ethylenically unsaturated carboxylic acid) and then combining the resulting polymer latex with an oxirane functional compound. In the polymer latex composition of the present invention, the carboxylic acid functional latex polymer of the present invention and the oxirane functional compound are present in relative amounts to provide a molar ratio of oxirane groups to carboxylic acid groups of from 0.1 to 2, preferably from 0.1 to 1.5, more preferably from 0.2 to 0.9, and most preferably from 0.3 to 0.6.
[0132] The oxirane functional compound may be selected from
[0133] i) a latex polymer with multiple oxirane functional groups, preferably a butadiene acrylonitrile latex polymer;
[0134] ii) a monomeric or oligomeric compound containing at least two oxirane functional groups; and
[0135] iii) Monomeric, oligomeric or polymeric compounds prepared by non-radical addition polymerization with at least one oxirane group and a functional group different from the oxirane group, which functional groups different from the oxirane group on different molecules of the compound iii) are capable of reacting with one another.
[0136] The latex polymer i) may be selected from ethylene oxide functional latex polymers as disclosed in WO 2017 / 209596.
[0137] Suitable monomeric or oligomeric compounds ii) containing at least two oxirane functional groups may be selected from ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, poly(ethylene glycol) diglycidyl ether, poly(propylene glycol) diglycidyl ether, bisphenol A diglycidyl ether and combinations thereof.
[0138] Preferably, compound iii) is selected from oxirane-functional di- or trialkoxysilanes, more preferably (3-glycidoxypropyl)trialkoxysilanes.
[0139] Without wishing to be bound by theory, it is believed that when an elastomeric film is formed from a latex composition containing the carboxylated polymer latex and the ethylene oxide functional compound of the present invention, thermally unstable β-hydroxy ester bonds (such as crosslinks) are formed. Upon application of thermal energy, these unstable β-hydroxy ester bonds or crosslinks can be broken and subsequently reformed again, with the result that such an elastomeric film exhibits self-healing properties and can be repaired and recycled, thereby providing additional advantages to the present invention.
[0140] Compounded latex composition for producing dip molded articles:
[0141] The polymer latex of the present invention is particularly suitable for use in a dip molding process. Thus, the polymer latex or polymer latex composition of the present invention is compounded to produce a curable polymer latex compound composition that can be used directly in a dip molding process.
[0142] The compounded latex composition suitable for producing a dip molded article comprises the polymer latex or polymer latex composition of the present invention and an auxiliary selected from a sulfur vulcanizing agent, an accelerator for sulfur vulcanization, a crosslinking agent, a multivalent cation, and a combination thereof. The multivalent cation (preferably ZnO) is present, preferably in an amount of 0.5 wt% to 2.5 wt% ZnO based on the solid latex polymer of ZnO.
[0143] In particular, the compounded latex composition may include 0 to 2.8 wt%, preferably 0.5 to 2.8 wt%, more preferably 1.0 to 2.0 wt%, most preferably 1.5 to 2.0 wt% sulfur, and 0.0 to 2.8 wt%, preferably 1.0 to 2.0 wt%, more preferably 1.2 to 1.8 wt% sulfur vulcanizing agent, and 0.5 wt% to 2.5 wt% ZnO, wherein the weight percentages are based on solid latex polymer. The sulfur vulcanizing agent may be omitted if a crosslinking agent (such as an oxirane functional compound as discussed above) is present.
[0144] In order to obtain reproducible good physical film properties, it is recommended to adjust the pH of the compounded polymer latex composition by a pH modifier to within the range of pH 7 to 13, preferably 10.5 to 13, more preferably 11 to 12 for dipping to produce thin disposable gloves. In order to produce unsupported and / or supported reusable gloves, it is recommended to adjust the pH of the compounded polymer latex composition by a pH modifier to within the range of pH 8 to 10, preferably 8.5 to 9.5. The compounded polymer latex composition contains the polymer latex of the present invention, optionally a pH modifier (preferably ammonia or an alkali metal hydroxide), and optionally conventional additives to be used for these compositions (selected from antioxidants, pigments, TiO2, fillers and dispersants).
[0145] In order to prepare the latex composition of the present invention, a variety of other additives and ingredients may be added. Such additives include, for example, defoamers, wetting agents, thickeners, plasticizers, fillers, pigments, dispersants, optical brighteners, antioxidants, biocides and metal chelators. Known defoamers include silicone oils and acetylene glycols. Conventional known wetting agents include alkylphenol ethoxylates, alkali metal dialkyl sulfosuccinates, acetylene glycols and alkali metal alkyl sulfates. Typical thickeners include polyacrylates, polyacrylamides, xanthan gum, modified cellulose or particulate thickeners (such as silica and clay). Typical plasticizers include mineral oil, liquid polybutene, liquid polyacrylate and lanolin. Titanium dioxide (TiO2), calcium carbonate and clay are typically used fillers. Proofreading
[0146] Method for making dip molded articles:
[0147] In the method for making the dip molding latex product of the present invention, first, a clean mold having the desired shape of the final product is immersed in a coagulant bath containing a metal salt solution. The coagulant is usually used in the form of a solution in water, alcohol or a mixture thereof. As a specific example of the coagulant, the metal salt can be a metal halide (like calcium chloride, magnesium chloride, barium chloride, zinc chloride and aluminum chloride); a metal nitrate (such as calcium nitrate, barium nitrate and zinc nitrate); a metal sulfate (such as calcium sulfate, magnesium sulfate and aluminum sulfate); and an acetate (such as calcium acetate, barium acetate and zinc acetate). Calcium chloride and calcium nitrate are most preferred. The coagulant solution may contain additives to improve the wetting behavior of the former.
[0148] Afterwards, the mold is removed from the bath and optionally dried. The mold thus treated is then immersed in the compounded latex composition of the present invention. Thus, a thin film of latex coagulates on the surface of the mold. It is known in the art that the thickness of the film thus impregnated can be influenced by the concentration of the compounded latex and / or the length of time the salt-coated mold is in contact with the compounded latex. Alternatively, the latex film can also be obtained by a dipping step, in particular two dipping steps in sequence.
[0149] Thereafter, the mold is removed from the latex composition and optionally immersed in a water bath to, for example, extract polar components from the composition and wash the coagulated latex film. Thereafter, the latex-coated mold is optionally dried at a temperature below 80°C.
[0150] Finally, in order to obtain the desired mechanical properties for the final film product, the latex coated mold is heat treated at a temperature of 40-180°C. Next, the final latex film is removed from the mold. The duration of the heat treatment will depend on the temperature and is typically between 1 and 60 minutes. The higher the temperature, the shorter the treatment time required.
[0151] The inventors of the present invention surprisingly discovered that when the polymer latex composition of the present invention is used, the dip molding process can be operated more economically. In particular, it was found that the duration between forming the compounded latex composition of the present invention and performing the dip molding step (ripening time) can be significantly reduced to 180 minutes or less compared to compounds made from standard latexes (requiring a ripening time of well over 180 minutes).
[0152] In addition, the inventors have found that the temperature in the heat treatment step can be significantly reduced to within the range of 40°C to less than 120°C without sacrificing the mechanical properties of the final dip molded product. Conventional latexes require temperatures of 120°C and above to achieve the desired mechanical properties. Therefore, when the polymer latex of the present invention is used, the dip molding process is less time-consuming and less energy-intensive, making it more economical.
[0153] The final heat treated elastomeric film may have a tensile strength of at least about 7 MPa and an elongation at break of at least about 300%, preferably a tensile strength of at least about 10 MPa, an elongation at break of at least about 350%, more preferably a tensile strength of at least about 15 MPa and an elongation at break of at least about 400%, and even more preferably a tensile strength of at least about 20 MPa and an elongation at break of at least about 500%. These mechanical properties are measured according to ASTM D 6319. A suitable range for stress retention is 35 to 80%, preferably 50 to 70%.
[0154] The dip molding process of the present invention can be used for any latex product that can be produced by a dip molding process known in the art. The product can be selected from health care devices, surgical gloves, examination gloves, condoms, catheters, or all kinds of industrial and household gloves formed by or including an elastomeric film. The polymer latex of the present invention is particularly suitable for preparing surgical gloves and condoms due to the improved stress retention of the elastomeric film obtained from the polymer latex of the present invention.
[0155] As mentioned above, elastomeric films made from polymer latex compositions containing the polymer latex of the present invention and an oxirane-functional compound can be repaired and recycled.
[0156] Methods for repairing elastomeric films and articles containing elastomeric films
[0157] The present invention also relates to a method for repairing an elastomeric film made from the polymer latex composition of the present invention by the following steps:
[0158] a) providing a damaged elastomeric film made from the polymer latex composition of the present invention or an article containing the damaged elastomeric film, the damaged elastomeric film having at least a surface to be reattached,
[0159] b) rejoining the damaged membrane surface,
[0160] c) heating or annealing the damaged elastomeric film at a temperature of 40° C. to 200° C. while maintaining intimate contact of the rejoined surfaces of the damaged film.
[0161] For the purpose of operation, the articles formed by the elastomeric film are collected and sorted, and selectively sterilized. Articles that are damaged but not to the extent that they cannot be reused are separated, and the damaged surface is optionally further cleaned. This cleaning can be done by washing with hydrogen peroxide or other sterilizing fluids or passing under a stream of carbon dioxide or UV light to ensure that no pathogens are present. At the damaged location, the surfaces of the damaged films that have been separated from each other are brought together so that they are in contact with each other, for example, if there is a hole, the edges of the hole are in contact and the surface is heated, so that the elastomeric film can be softened and the surface is sealed together to repair the damage, after which the surface is allowed to cool and reveal the repaired or self-repaired surface. Pressure can be applied to the contact area of the damaged surface to heat it.
[0162] Method for recycling elastomeric film or articles containing the same
[0163] The present invention also relates to a method for recycling an elastomeric film or an article containing the elastomeric film made from the polymer latex composition of the present invention, by cutting, shredding or crushing the elastomeric film or article to form particles of the elastomer, optionally blending the resulting particles with particles of virgin elastomer, and forming the recycled film or article by subjecting the particles to a pressure of 1-20 MPa and a temperature of 40°C to 200°C.
[0164] Collect elastic materials (such as gloves), and if necessary, classify them so that nitrile-containing materials are collected together, while other materials are discarded or sent to alternative recycling or reprocessing facilities. The collected materials are then cleaned and decontaminated (if necessary), which is very similar to the repair / self-repair process. The material is then crushed into a particle size of no more than 2 mm average diameter, preferably no more than 1 mm average diameter and ideally in the range of 0.15 to 0.75 diameter, more preferably 0.2 to 0.3 average diameter particle size. Can be less than room temperature or indeed under cryogenic conditions to carry out crushing or grinding process, so that processing is easy and before further processing, keep the material as particles. Cooling conditions avoid any re-engagement of the particles until needed. Can be stored at room temperature or under such conditions that the particles are avoided to be re-engaged until needed. Can be fed to a blender (wherein blending the material with other materials such as particles of virgin elastomeric materials and conventional processing aids and additives), before further grinding the material. If there is no blending step, the material is fed directly to a thermal processing system where the particles / crumbs are hot pressed, 2-roll milled, calendered or extruded under pressure and under heating conditions (i.e., over 40 degrees Celsius) to allow the material to flow as a result of the bonds within the material (e.g., bonds within the β-hydroxy esters of the material) being broken, and the material can also be molded into the desired final shape at this stage. The material is then optionally cooled in a mold or as part of an extrusion process to produce a final product formed from the recycled material.
[0165] The present invention is further illustrated with reference to the following examples. Example:
[0166] Determination of physical parameters:
[0167] The dispersions were characterized by determining the total solids content (TSC), pH, viscosity (Brookfield LVT) and z-average particle size. Furthermore, the tensile properties of the final films were tested.
[0168] Determination of total solid content (TSC):
[0169] The determination of the total solid content is based on gravimetric analysis. 1-2 g of the dispersion is weighed on an analytical balance into a weighed aluminum dish. The dish is stored in a circulating air oven at 120° C. for 1 hour until a constant mass is reached. After cooling to room temperature, the final weight is then determined again. The solid content is calculated as follows:
[0170]
[0171] Among them, m 初始 = initial mass of latex,
[0172] m 最终 = Mass after drying
[0173] Determination of pH value:
[0174] The pH value was determined in accordance with DIN ISO 976. After carrying out a 2-point calibration using the buffer solution, the electrode of a Schott CG 840 pH meter was immersed in the dispersion at 23° C. and the constant value on the display was recorded as the pH value.
[0175] Determination of viscosity:
[0176] At 23°C, use a Brookfield LVT viscometer to measure latex viscosity. Fill a 250 ml beaker with about 220 ml of liquid (without bubbles) and immerse the viscometer's spindle to the mark on the spindle. Then turn on the viscometer and record the value after about 1 minute until it is constant. The viscosity range determines the choice of spindle and speed and the factors used to record the values to calculate the viscosity. Information about the spindle and revolutions per minute used is shown in brackets in the examples.
[0177] Determination of particle size (PS):
[0178] The z-average particle size was measured using a Malvern Zetasizer Nano S (ZEN 1600) using dynamic light scattering. The latex sample was diluted with deionized water to the turbidity level described in the manual and transferred to a test colorimetric tube. The tube was gently mixed to homogenize the sample and placed in the measuring device. The value was recorded as the z-average particle size generated by the software.
[0179] Preparation of impregnated membrane
[0180] Unless otherwise stated in the individual examples below, the nitrile latex and compounding materials were stirred at room temperature at the desired pH for 24 hours and then the coagulant was impregnated as follows:
[0181] A ceramic spade was cleaned with soap and then rinsed thoroughly with deionized water before drying in an air circulating oven set at 65-70°C (spade temperature, 55-60°C) until dry.
[0182] A solution of coagulant was prepared by dissolving calcium nitrate (18 wt%) and calcium carbonate (2 wt%) in deionized water.
[0183] The dry spatula was then dipped into the salt solution, removed and then dried in an air circulation oven set at 70-75° C. (shovel temperature, 60-65° C.) until dry. The salt-coated spatula was then dipped into the desired compounded latex (which had a total solids content of 18 wt% and was aged at room temperature for 24 hours after compounding) for a residence time of 5 seconds, after which it was removed and the latex-coated spatula was placed in an air circulation oven set at 100° C. for 1 minute to gel the film.
[0184] The thus gelled film was then rinsed in a bath of deionized water set to 50-60°C for 1 minute before curing in an air circulating oven set to 120°C for 20 minutes; thereafter, the thus cured / vulcanized film was cooled and removed from the spatula before aging in an air circulating oven set to 100°C for 22 hours.
[0185] Finally, the cured film was manually peeled off from the spatula, with a typical dry film thickness of 0.056-0.066 mm.
[0186] Films prepared from this latex were tested for their tensile strength properties and stress retention behavior.
[0187] Determination of tensile strength properties
[0188] The tensile properties of the vulcanized films / gloves were tested according to ASTM 6319, dumbbell specimens were cut from the gloves prepared from each latex compound using an ASTM D412 Type C cutter (width of narrow portion = 6 mm, length of narrow portion = 33 mm, total length = 115 mm, the thickness of the dumbbell is listed in the results table) and tested on a Hounsfield HK10KS tensiometer equipped with a H500LC extensometer at an elongation rate of 500 mm / min.
[0189] Determination of stress retention properties
[0190] The tensile stress was measured on the dumbbell sample by a tensiometer (same as mentioned above). The stress retention (%) was defined as the ratio (%) of I6 / I0×100, where I0 is the initial stress measured immediately after the elongation reaches 100%, and I6 is the stress measured after the specimen is maintained at 100% elongation for 6 minutes.
[0191] The following abbreviations are used in the examples:
[0192] MAA = Methacrylic Acid
[0193] Bd = Butadiene
[0194] ACN = Acrylonitrile
[0195] tDDM = tert-dodecyl mercaptan
[0196] Na4EDTA = Tetrasodium salt of ethylenediaminetetraacetic acid
[0197] TSC = Total Solids Content
[0198] PS = particle size
[0199] ZnO=zinc oxide
[0200] ZDEC = Zinc diethyldithiocarbamate
[0201] S = Sulfur
[0202] Unless otherwise indicated, all parts and percentages listed below are by weight.
[0203] Example 1: Preparation of dip-coated membrane (control example)
[0204] 2 parts by weight (based on polymer solids) of seed latex (average particle size 36 nm) and 807 parts by weight of water (based on 100 parts by weight of the monomers including the seed latex) were added to a nitrogen purged autoclave and subsequently heated to 30°C. Next, 0.01 parts by weight of Na4EDTA and 0.005 parts by weight of Bruggolite FF6 dissolved in 2 parts by weight of water were added, followed by 0.08 parts by weight of sodium persulfate dissolved in 2 parts by weight of water. Next, over a period of 6 hours, monomers (35 parts by weight of acrylonitrile, 57 parts by weight of butadiene, 6 parts by weight of methacrylic acid) were added together with 0.6 parts by weight of tDDM. Over a period of 10 hours, 2.2 parts by weight of sodium dodecylbenzene sulfonate, 0.2 parts by weight of tetrasodium pyrophosphate, and 22 parts by weight of water were added. A co-activator feed of 0.13 parts by weight of Bruggolite FF6 in 8 parts by weight of water was added over 9 hours. The temperature was maintained at 30°C until 95% conversion, resulting in a total solids content of 45%. The polymerization was briefly stopped by adding 0.08 parts by weight of a 5% aqueous solution of diethylhydroxylamine. The pH was adjusted to pH 7.5 using potassium hydroxide (5% aqueous solution) and residual monomers were removed by vacuum distillation at 60°C. 0.5 parts by weight of Wingstay L-type antioxidant (60% dispersion in water) was added to the raw latex and the pH was adjusted to 8.2 by adding 5% aqueous solution of potassium hydroxide.
[0205] With respect to Example 1, the following characterization results were obtained:
[0206] TSC=45.0wt.%
[0207] pH=8.2
[0208] Tg=-15℃
[0209] Viscosity = 30.5 mPas (1 / 60)
[0210] Particle size, P z =120nm
[0211] Prior to gelling of the film at 100°C for 1 minute, the dried, salt-coated spatula was dipped into a diluted compounded latex solution with 18% TSC (containing 0.8 phr S, 0.7 phr ZDEC, 1 phr ZnO and titanium dioxide at pH 10) with a residence time of 5 seconds, rinsed with deionized water for 1 minute (in a bath set at 50-60°C) for 1 minute, followed by drying and curing / vulcanization in an air circulating oven set at 120°C for 20 minutes to ensure complete drying and cross-link formation.
[0212] The tensile and stress retention properties are shown in Table 1 below.
[0213] Example 1a
[0214] Example 1 was repeated except that the impregnation was performed as follows.
[0215] Prior to gelling the film at 100°C for 3 minutes, the dried, salt-coated spatula was dipped into a diluted compounded latex solution with 18% TSC (containing 1.5 phr S, 1.2 phr ZDEC, 0.9 phr ZnO and titanium dioxide at pH 10) with a residence time of 5 seconds, rinsed with deionized water for 1 minute (in a bath set at 50-60°C) for 1 minute, followed by drying and curing / vulcanization in an air-circulating oven set at 120°C for 20 minutes to ensure complete drying and cross-link formation. The tensile and stress retention properties are shown in Table 1 below.
[0216] Example 2: (Replacement of 10% of MAA)
[0217] A composition was prepared in the same manner as in Example 1, except that 5.4 parts of methacrylic acid and 0.6 parts of β-CEA (a mixture of 2-carboxyethyl acrylate oligomers commercially available from Solvay (Belgium).
[0218] Example 3: (Replacement of 20% of MAA)
[0219] A composition was prepared in the same manner as in Example 1, except that 4.8 parts of methacrylic acid and 1.2 parts of β-CEA.
[0220] Example 4: (Replacement of 30% of MAA)
[0221] A composition was prepared in the same manner as in Example 1, except that 4.2 parts of methacrylic acid and 1.8 parts of β-CEA.
[0222] Example 5: (Replacement of 40% of MAA)
[0223] A composition was prepared in the same manner as in Example 1, except that 3.6 parts of methacrylic acid and 2.4 parts of β-CEA.
[0224] Example 6: (100% use of 2-carboxyethyl acrylate oligomer)
[0225] A composition was prepared in the same manner as in Example 1, except that methacrylic acid was not used and 6 parts of β-CEA.
[0226] Example 6a (100% use of 2-carboxyethyl acrylate oligomer)
[0227] A composition was prepared in the same manner as in Example 1a, except that no methacrylic acid was used and 6 parts of β-CEA.
[0228] Example 7: (100% 2-carboxyethyl acrylate oligomer, compounding formula V1)
[0229] A composition was prepared in the same manner as in Example 1, except that methacrylic acid was not used and 6 parts of In addition, the compounded latex formulation contained 0.9 phr of ZnO, 1.5 phr of S and 1.2 phr of ZDEC.
[0230] Example 8: (100% use of 2-carboxyethyl acrylate oligomer, using compounding formula V1 with longer curing time)
[0231] A composition was prepared in the same manner as in Example 1, except that methacrylic acid was not used and 6 parts of β-CEA. In addition, the compounded latex formulation contained 0.9 phr ZnO, 1.5 phr S and 1.2 phr ZDEC. Curing / vulcanization was performed for 35 minutes instead of 20 minutes.
[0232] Example 9 (100% use of 2-acryloyloxyethyl succinate)
[0233] A composition was prepared in the same manner as in Example 1a, except that no methacrylic acid was used and 6 parts of 2-acryloyloxyethyl succinate were used.
[0234] Table 1
[0235]
[0236] Example 10: (Control Example, Gloves with High Thickness)
[0237] This example is an exact repeat of Example 1.
[0238] Example 11: (100% 2-carboxyethyl acrylate oligomer, gloves with high thickness, curing time 35 minutes, compounding formula V1)
[0239] A composition was prepared in the same manner as in Example 1, except that methacrylic acid was not used and 6 parts of β-CEA. In addition, the compounded latex was not diluted and the compounded formula contained 0.9 phr ZnO, 1.5 phr S and 1.2 phr ZDEC. Curing / vulcanization was performed for 35 minutes instead of 20 minutes.
[0240] Example 12: (100% 2-carboxyethyl acrylate oligomer, gloves with high thickness, curing time 40 minutes, compounding formula V1)
[0241] A composition was prepared in the same manner as in Example 1, except that methacrylic acid was not used and 6 parts of β-CEA. In addition, the compounded latex was not diluted and the compounded formula contained 0.9 phr ZnO, 1.5 phr S and 1.2 phr ZDEC. Curing / vulcanization was performed for 40 minutes instead of 20 minutes.
[0242] Example 13: (100% 2-carboxyethyl acrylate oligomer, gloves with high thickness, curing time 1 50 minutes, compounding formula V1)
[0243] A composition was prepared in the same manner as in Example 1, except that methacrylic acid was not used and 6 parts of β-CEA. In addition, the compounded latex was not diluted and the compounded formula contained 0.9 phr ZnO, 1.5 phr S and 1.2 phr ZDEC. Curing / vulcanization was performed for 50 minutes instead of 20 minutes.
[0244] The tensile and stress retention properties of Examples 8-12 are shown in Table 2 below.
[0245] Table 2
[0246]
[0247] Example 14: (Comparative Example with 48 Hours of Ripening Time)
[0248] The composition was prepared in the same manner as in Example 1, except that methacrylic acid was not used and the latex was compounded with stirring at room temperature for 48 hours, rather than 24 hours, prior to impregnation.
[0249] Example 15: (100% 2-carboxyethyl acrylate oligomer, curing time 35 minutes, compounding formula V2)
[0250] A composition was prepared in the same manner as in Example 1, except that methacrylic acid was not used and 6 parts of β-CEA. In addition, the compounded latex formulation contained 0.3 phr ZnO, 2 phr S and 0.5 phr ZDEC. Before dipping, the compounded latex was stirred at room temperature for 48 hours (hrs) instead of 24 hours (hrs). Curing / vulcanization was performed for 35 minutes instead of 20 minutes.
[0251] Example 16: (100% 2-carboxyethyl acrylate oligomer, curing time 35 minutes, compounding formula V3)
[0252] A composition was prepared in the same manner as in Example 1, except that methacrylic acid was not used and 6 parts of β-CEA. In addition, the compounded latex formulation contained 0.3 phr ZnO, 2 phr S and 1 phr ZDEC. Before dipping, the compounded latex was stirred at room temperature for 48 hours instead of 24 hours. Curing / vulcanization was performed for 35 minutes instead of 20 minutes.
[0253] The tensile and stress retention properties of Examples 13 to 15 are shown in Table 3 below.
[0254] Table 3
[0255]
Claims
1. A polymer latex composition comprising a polymer latex for preparing an elastomeric film obtainable by free radical emulsion polymerization of a mixture of ethylenically unsaturated monomers, the mixture comprising: a) 15 to 99 wt% of a conjugated diene; b) 0 to 80 wt % of an ethylenically unsaturated nitrile compound; c) 0 to 70 wt% of a vinyl aromatic monomer; The sum of the ethylenically unsaturated nitrile compound b) and the vinyl aromatic monomer c) is 0.95 to 84.95 wt %, d) 0.05 to 10 wt% of an ethylenically unsaturated acid, wherein the ethylenically unsaturated acid comprises d1) contains the following ethylenically unsaturated acids: - an acid functional group; and - a spacer group separating the ethylenically unsaturated group from the acid functional group by at least 4 atoms; and e) 0 to 65 wt % of a copolymerizable ethylenically unsaturated compound, wherein the monomers a) to e) are different from one another and the weight percentages are based on the total monomers in the mixture; wherein the ethylenically unsaturated acid of d1) is present in an amount of 0.05 to 10 wt % based on the total monomers in the mixture, The monomer d) comprises an ethylenically unsaturated carboxylic acid and the composition further comprises an oxirane-functional compound.
2. The polymer latex composition of claim 1, wherein the acid functional group is selected from the group consisting of a carboxylic acid group and a phosphorus-containing acid group.
3. The polymer latex composition of claim 1, wherein d1) is selected from compounds having the following structures: CHR 2 =CR 1 -A-X, in R 1 is selected from H and C1-C4 alkyl, R 2 Selected from H or -AX; A is a divalent spacer group separating the ethylenically unsaturated group from the functional group X by at least 4 atoms, which are independently selected when each occurs: -(C(O)-W) n -Y-(O) m -;-(C(O)-W) n -Y-O-C(O)-Y- and -(CH2) k -O-(C(O)) p -Y-(O) m -, n, m, k and p, when each occurs, are integers independently selected from 0 or 1; W is -O- or -NR 3 -; R 3 Selected from H and C1-C4 alkyl; Y is independently selected from optionally substituted linear, branched, cyclic C2 to C 30 divalent hydrocarbon or heterohydrocarbon group; X is selected from -C(O)OH and -P(O)(OH)2; Provided that: if X is -C(O)OH then m is 0; or -AX is selected from -C(O)-O-(YC(O)-O) l -H, wherein l is an integer from 2 to 10; and A mixture of them.
4. The polymer latex composition of claim 1, wherein the ethylenically unsaturated acid of d1) is the only ethylenically unsaturated acid.
5. The polymer latex composition of claim 1, wherein the ethylenically unsaturated acid d) further comprises an ethylenically unsaturated acid d2) selected from the group consisting of: - ethylenically unsaturated carboxylic acids and their salts, - ethylenically unsaturated polycarboxylic anhydrides; - Polycarboxylic acid partial ester monomers and their salts.
6. The polymer latex composition of claim 1, wherein a) the conjugated diene is selected from butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, myrcene, ocimene, farnesene and combinations thereof, b) the ethylenically unsaturated nitrile compound is selected from (meth)acrylonitrile, α-cyanoethylacrylonitrile, fumaronitrile and combinations thereof; c) the vinyl aromatic monomer is selected from the group consisting of styrene, α-methylstyrene, vinyltoluene, and combinations thereof; and e) the copolymerizable ethylenically unsaturated compound is selected from e1) alkyl esters of ethylenically unsaturated acids; e2) hydroxyalkyl esters of ethylenically unsaturated acids; e3) amides of ethylenically unsaturated acids; e4) vinyl carboxylates; e5) alkoxyalkyl esters of ethylenically unsaturated acids, e6) monomers having at least 2 ethylenically unsaturated groups; e7) Ethylenically unsaturated silanes and combinations thereof.
7. The polymer latex composition of claim 1, wherein the ethylenically unsaturated monomer mixture used in the polymer latex comprises: a) 20 to 98 wt% of a conjugated diene; b) 1 to 60 wt % of an ethylenically unsaturated nitrile compound; c) 0 to 40 wt% of a vinyl aromatic monomer; d) 1 to 8 wt% of an ethylenically unsaturated acid; e1) 0 to 25 wt% of C1-C8 alkyl (meth)acrylate; e3) 0 to 10% by weight of amides of ethylenically unsaturated acids, e4) 0 to 10 wt% of vinyl ester, e7) 0 to 10 wt % of ethylenically unsaturated silanes, The weight percentages are based on the total monomers in the mixture.
8. Use of the polymer latex composition of claim 1 for producing dip-molded articles or for coating or impregnating substrates.
9. The polymer latex composition of claim 1, wherein the oxirane functional compound is selected from i) latex polymer; ii) a monomeric or oligomeric compound containing at least two oxirane functional groups; and iii) Monomeric or polymeric compounds prepared by non-radical addition polymerization with at least one oxirane group and a functional group different from the oxirane group, said functional groups different from the oxirane group being capable of reacting with one another on different molecules of the compound iii).
10. The polymer latex composition of claim 1, wherein the carboxylic acid functional latex polymer and the ethylene oxide functional compound are present in relative amounts to provide a molar ratio of ethylene oxide groups to carboxylic acid groups of from 0.1 to 2.
11. A compounded latex composition suitable for producing dip molded articles, comprising the polymer latex composition of claim 1 and an auxiliary selected from the group consisting of a sulfur vulcanizing agent, an accelerator for sulfur vulcanization, a crosslinking agent, a multivalent cation, and combinations thereof.
12. The compounded latex composition of claim 11, comprising 0 to 2.8 wt% sulfur, and 0 to 2.8 wt% sulfur vulcanizing agent, and 0.5 to 2.5 wt% ZnO, wherein the weight percentages are based on solid latex polymer.
13. A method for producing a dip-molded article by the following steps: a) providing the compounded latex composition of claim 11; b) immersing a mold having the desired shape of the final article in a coagulant bath containing a metal salt solution; c) removing the mold from the coagulant bath and optionally drying the mold; d) dipping the mold treated as in steps b) and c) into the compounded latex composition of step a); e) coagulating a latex film on the mold surface; f) removing the latex-coated mold from the compounded latex composition and optionally immersing the latex-coated mold in a water bath; g) optionally drying the latex-coated mold; h) heat treating the latex coated mold obtained from step e) or f) at a temperature of 40° C. to 180° C.; and i) Removing the latex article from the mould.
14. The method of claim 13, wherein after step a) and before step d), the compounded latex composition is aged for at least 3 hours.
15. An elastomeric film produced from the latex composition of claim 1 or the compounded latex composition of claim 11.
16. An article comprising the elastomeric film of claim 15 selected from the group consisting of surgical gloves, examination gloves, condoms, catheters, industrial gloves, textile-supported gloves, and household gloves.
17. A method of repairing the elastomeric film of claim 15 prepared from the latex composition of claim 1 or the article of claim 16 comprising the elastomeric film of claim 15 prepared from the latex composition of claim 1 by the following steps: a) providing a damaged elastomeric film of claim 15 prepared from the latex composition of claim 1 or an article containing a damaged elastomeric film of claim 16 comprising the elastomeric film of claim 15 prepared from the latex composition of claim 1, the damaged elastomeric film having at least a surface to be reattached, b) rejoining the surface of the damaged film, c) heating or annealing the damaged elastomeric film at a temperature of 40° C. to 200° C. while maintaining intimate contact of the rejoined surfaces of the damaged film.
18. A method for recycling the elastomeric film of claim 15 prepared from the latex composition of claim 1 or the article of claim 16 comprising the elastomeric film of claim 15 prepared from the latex composition of claim 1 by the following steps: cutting, chopping or pulverizing the elastomeric film or article to form particles of the elastomer, optionally blending the resulting particles with particles of virgin elastomer, and forming the recycled film or article by subjecting the particles to a pressure of 1-20 MPa and a temperature of 40°C to 200°C.
Citation Information
Patent Citations
Process for preparing a latex based on conjugated dienes by emulsion polymerization
EP0792891A1
Dip-forming latex, dip-forming composition and dip-formed article
US20050154122A1
High stress retention nitrile glove
US20170099889A1
Soft nitrile zinc oxide free medical gloves
US6451893B1
Double dipped gloves
US7730554B2